Notes on the Western Palaearctic genus Leptocharis Reitter (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
A morphological study of the Western Palaearctic genus Leptocharis Reitter revealed remarkable differences between L. microphthalmus Meybohm and all remaining congeners. This species is the only Eurasian member of Stenichnini with the mesocoxae not separated by the mesoventral process. A new genus, Turkocharis gen. n., is proposed to accommodate L. microphthalmus. Morphological details of both Leptocharis and Turkocharis are illustrated and discussed, and the Nearctic genus Neladius Casey is indicated as morphologically most similar to the presumably closely related Leptocharis and Turkocharis. As the genus name Leptocharis is of a feminine grammatical gender, specific adjectives previously with masculine endings are corrected to Leptocharis algerica Besuchet, L. cretica (Pic), and Turkocharis microphthalma (Meybohm) comb. n. An updated key for identification of the Eurasian and New Guinean genera of Stenichnini is given.